2022
DOI: 10.48550/arxiv.2202.00591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Chemo-Dynamical Groups of Galactic Globular Clusters

Thomas M. Callingham,
Marius Cautun,
Alis J. Deason
et al.

Abstract: We introduce a multi-component chemo-dynamical method for splitting the Galactic population of Globular Clusters (GCs) into three distinct constituents: bulge, disc, and stellar halo. The latter is further decomposed into the individual large accretion events that built up the Galactic stellar halo: the Gaia-Enceladus-Sausage, Kraken and Sequoia structures, and the Sagittarius and Helmi streams. Our modelling is extensively tested using mock GC samples constructed from the auriga suite of hydrodynamical simula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 85 publications
(130 reference statements)
2
8
0
Order By: Relevance
“…The mass of this GC translates into M host galaxy ≈ 1.3 × 10 9 M for its former host galaxy. Such M value is well within the literature range for GSE (see Figure 6) and is more than 10 times larger than the expected value for Sequoia of ∼5−8 × 10 7 M (Myeong et al 2019;Forbes 2020;Kruijssen et al 2020;Callingham et al 2022). Following this line of thought, it would be natural to imagine GSE as a stronger candidate as the host of such a robust NSC.…”
Section: The Case Of ωCen and Ngc 1851supporting
confidence: 82%
See 2 more Smart Citations
“…The mass of this GC translates into M host galaxy ≈ 1.3 × 10 9 M for its former host galaxy. Such M value is well within the literature range for GSE (see Figure 6) and is more than 10 times larger than the expected value for Sequoia of ∼5−8 × 10 7 M (Myeong et al 2019;Forbes 2020;Kruijssen et al 2020;Callingham et al 2022). Following this line of thought, it would be natural to imagine GSE as a stronger candidate as the host of such a robust NSC.…”
Section: The Case Of ωCen and Ngc 1851supporting
confidence: 82%
“…These authors demonstrated that GCs of GSE, selected from dynamics alone, follow a track in AMR clearly separated from their in situ counterparts, being more metal-poor within the same age interval (data from Forbes & Bridges 2010). These results were confirmed and expanded with new DRs from Gaia by many subsequent studies (Massari et al 2019;Forbes 2020;Horta et al 2020;Kruijssen et al 2020;Callingham et al 2022).…”
Section: Candidates In the Literaturesupporting
confidence: 61%
See 1 more Smart Citation
“…For instance, Wukong's star counts are ≈ 2.5% of those of GSE, and so we infer its mass is ≈ 1.3 × 10 7 M . We choose GSE as the reference object to derive other systems' masses because its stellar mass has been estimated via multiple independent methods that agree well with each other (e.g., Helmi et al 2018;Kruijssen et al 2020;Mackereth & Bovy 2020;Naidu et al 2021;Callingham et al 2022), and because it is fairly well mixed within the H3 Survey footprint (Han et al 2022). As a sanity check, based on this method, Sgr would have an inferred stellar mass of ≈ 3 × 10 8 M , which is in excellent agreement with various literature estimates that span ≈ 2 − 6 × 10 8 M (e.g., Niederste-Ostholt et al 2010;Law & Majewski 2010;Kruijssen et al 2020;Vasiliev & Belokurov 2020), and within a factor of 2 of our adopted value (6 × 10 8 M ) from Laporte et al 2018.…”
Section: Disrupted Galaxy Samplementioning
confidence: 99%
“…Recent studies (Trujillo-Gomez et al 2021;Wu et al 2021;Callingham et al 2022) focusing on the kinematics of GCs and halo stars have shown that orbital actions and integral of motions are useful probes of the dynamical histories of galaxies. These quantities are generally conserved during the slow evolution of the gravitational potential (Binney & Tremaine 2008).…”
Section: Orbital Actionsmentioning
confidence: 99%